LASER DOPPLEROGRAPHIC FLOWMETRY IN ASSESSMENT OF FUNCTIONAL CONDITION OF THE SKIN MICROVESSELS IN PATIENTS WITH MICROVASCULAR ANGINA - I. E. Karpova; A. A. Fedorovich; G. N. Soboleva; L. E. Samoylenko; A. N. Rogoza; Yu. A. Karpov (Российский кардиологический журнал)
Aim. To study functional condition of the skin microvessels by laser doppler flowmetry (LDF) with functional tests comparing to the parameters of myocardial flow reserve by the data of single-photon emission computed tomography (SPECT) in patients with microvascular angina (MVA).Material and methods. Totally 44 patients with MVA included at the age of 58 [51;62] years and 30 healthy voluteers. LDF was performed on the skin of forearm with functional tests and perfusion SPECT with exercise or pharmacological test with sodium adenosinetriphosphate.Results. By LDF of the skin data and warm test, in patients with MVA there is statistically significant decrease of dilatatory microcirculatory reserve comparing to healthy subjects. A relationship is revelaled of dilatatory potential by LDF of the skin with electrical stimulation, and the parameters of myocardial perfusion reserve by SPECT of myocardium with exercise test in MVA.